Role of Biotechnology in Biotic Stress Management in Crops - P. Ananda Kumar (International Journal of Economic Plants)
Genetic improvement of crop plants through conventional plant breeding has made tremendous contributions to the breakthrough in the global agricultural production. Currently transgenic crops are produced in more or less routine manner. Dramatic progress in transformation techniques has widened the genetic base across the species barriers. The global area of genetically improved agricultural crops has seen a tremendous increase since its first adoption in 1996 to 170 million hectares in 2013. Management of biotic stresses (insect pests and pathogens) in agriculture is important to safeguard crop yields and productivity. Transgenic crops resistant to insect pests and viral diseases have been commercialized with substantial benefits to the farmers which helps to minimize the use of chemical pesticides. The world’s population is expected to reach 8.0 billions by the year 2050, making food security the most important social issue. Conventional technologies of agriculture are inadequate to meet the formidable challenges. Advances in modern biology, especially biotechnology, offer many advantages over traditional techniques of plant breeding. Some of the above problems could be addressed through molecular marker-assisted breeding. In addition, genetic transformation is an approach that can dramatically speeds up plant breeding. Plant biotechnology has made significant strides in the past twenty years. Development of efficient procedures of genetic transformation led to the introduction of several transgenics in all major crop species. A variety of traits have been introduced in many crops. More than a dozen GM crops are cultivated globally. Marker assisted selection has given rise to commercial products such as Blight resistant rice, Downy mildew resistant Bajra, submergence tolerant rice etc., Unraveling of genomes aided by innovations and discoveries in bioinformatics would only hasten such efforts. Intensive and all round efforts are needed to meet the challenges of feeding the future populations. Integration of modern biology, plant breeding, computational biology, phonemics and related tools will make the endeavors possible.